การศึกษากลยุทธ์และประสิทธิผลของโครงการประชาสัมพันธ์ เพื่อลดอุบัติเหตุจราจรจากการดื่มสุรา - ทิพารัตน์ เด่นชัยประดิษฐ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
The main objective of this research was to study the strategies used in public relations and communication campaign to prevent traffic accident caused by alcohol drinking. Its effectiveness was also examined through assessing samples exposure to this campaign, knowledge and attitude toward traffic accident caused by alcohol drinking, and driving behavior after alcohol drinking. Questionnaires were used to collect data from the Bangkok inhabitants selected 390 samples. The results of the study revealed that the principal strategies were to release information through variety of mass media channels on traffic accident caused by alcohol drinking in order to establish the awareness of the problems especially in print media and to organize public relations activities to gain campaign s audience participation. as for the campaign effectiveness, the research showed that most samples had limited exposure to this campaign. Their knowledge towards traffic accident caused by alcohol drinking was limited. However, their attitude towards traffic accident caused by alcohol drinking was positive. Their driving behavior after alcohol drinking was low safety. Furthermore, demographic characteristics can not expain differences in media exposure to this campaign. Media exposure did not correlate with knowledge towards traffic accident caused by alcohol drinking and driving behavior after alcohol drinking. But, there were negative correlations between media exposure and attitude towards traffic accident caused by alcohol drinking.